2017
DOI: 10.1002/pbc.26458
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of intraoperative frozen section for the diagnosis of renal tumors suspicious for malignancy in children and adolescents

Abstract: Background The ability of Intraoperative Frozen Section (IFS) to reliably diagnose renal tumors in children and adolescents is largely unknown. The objective of our study is to evaluate the ability of IFS to establish a histologic diagnosis for renal tumors in this population. Methods We reviewed our experience with patients who underwent IFS at the time of surgery for a renal tumor suspicious for malignancy from 2005–15. The IFS was compared to the final pathology (FP). Data on concordance and reliability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Carrasco et al showed that IFS on a nephrectomy specimen is a reliable method to determine final pathology for the diagnosis of renal tumors at the time of resection, with a sensitivity and specificity for correct identification of tumor histology of 0.92 and 1, respectively. 22 Additionally, they reported that IFS correctly distinguished between WT and non-WT cases in 94% of cases. Thus, IFS could help in “real time” by analyzing the NSS resection specimen after excision to determine if a small tumor is WT or other RN-appropriate histology.…”
Section: Discussionmentioning
confidence: 99%
“…Carrasco et al showed that IFS on a nephrectomy specimen is a reliable method to determine final pathology for the diagnosis of renal tumors at the time of resection, with a sensitivity and specificity for correct identification of tumor histology of 0.92 and 1, respectively. 22 Additionally, they reported that IFS correctly distinguished between WT and non-WT cases in 94% of cases. Thus, IFS could help in “real time” by analyzing the NSS resection specimen after excision to determine if a small tumor is WT or other RN-appropriate histology.…”
Section: Discussionmentioning
confidence: 99%